Pemetaan Potensi Pembangkit Listrik Tenaga Surya Rooftop pada Atap Gedung Perkantoran di Kabupaten Toraja Utara - Duma, Stefanus; Ambabunga, Yusri; Pawarangan, Ishak; Idris, Lalu Mohammad Junaidi (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2025)
A solar power plant or PLTS is a power generation system that utilizes sunlight as an energy source. PLTS power plants have the potential to be developed in Indonesia due to the working principles of PLTS which are environmentally friendly and have a low level of pollution and are included in renewable energy. In this study, a mapping of the potential of PLTS was carried out in the office building of the North Toraja Marante Joint Service Office and the North Toraja Panga' Regent's Office, where in this study the total roof area of ​​the North Toraja Marante Joint Service Office building was 2,595,770545 m2 and the Office building The Regent of North Toraja Panga' resulted in a roof area of ​​4238.563246 m2 from the calculated roof area data, the PV modules that can be installed on the North Toraja Marante Joint Service Office building are 116 pcs and on the North Toraja Panga' Regent Office building the potential is 193 pcs. So that it can be obtained PV out in the North Toraja Marante Joint Office building of 0.052 MWh per day and 18,937 MWh per year and PV out in the North Toraja Panga' Regent's Office building of 0.087 MWh per day and 31.484 MWh per year. The results of this study are expected to be developed for further research to calculate the potential of PV mini-grid.